-5x-6x=-5+3

Simple and best practice solution for -5x-6x=-5+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x-6x=-5+3 equation:


Simplifying
-5x + -6x = -5 + 3

Combine like terms: -5x + -6x = -11x
-11x = -5 + 3

Combine like terms: -5 + 3 = -2
-11x = -2

Solving
-11x = -2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-11'.
x = 0.1818181818

Simplifying
x = 0.1818181818

See similar equations:

| 45+4*12=61+4*12 | | 4y-6=3y+25 | | 3m^2+72=33m | | -6(-7x-1)=-8x+9(-3x-4) | | 13-8x+1139=0 | | x^2+49=6 | | 2(1+7x)-3(x-3)=+55 | | 2x+5=-75+8x | | 2x+5=20-x | | -18-9m=m^2 | | 6x+22=14x-17 | | 1/3-40.90 | | 5x+30=10x+40 | | 40.90-1/3 | | 13x^2+11x-24=0 | | -7(8k-4)-7(k-6)=7 | | -7(8k-4)-7(k-6)= | | 3x+1/2-x=6x-4/7 | | y+3=-1/5(x-6) | | -4x+4x=11-4-2-5 | | x+4/3y=-5 | | 289=256x^2+81x^2 | | r^2-7r=8 | | 6.8(x-1)=-0.2x+42.2 | | (30x^3)=0 | | (30x^2)=0 | | 30x^2=0 | | (30x^4)=0 | | x^2+54x+728=0 | | +12-13=45+12 | | x^2+54x+727=0 | | (30x^4)(x-1)=0 |

Equations solver categories